Long-term rain attenuation probability and site diversity gain prediction formulas [electronic resource] - 242616 Kusay Faisal A. Al-Tabatabaie (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2007